Factors Influencing Contrast Enhancement in Abdominal Computed Tomography Angiography in the Dog: A Systematic Review - Simone Perfetti; Carlo Guglielmini; Nikolina Linta; Alessia Diana (Animals)
Multidetector-row computed tomographic angiography (angio-CT) aims to achieve optimal opacification of the vascular compartment of interest. The distribution and quality of vascular opacification are influenced by patient-related factors, contrast medium (CM)-related factors, and scanner-related factors. This systematic review evaluates these factors and their effects on contrast enhancement. A comprehensive literature search was made in February 2024 across four online bibliographic databases (Web of Science, PubMed, Scopus, and CAB Abstract) in adherence with the PRISMA 2020 guidelines. After screening the 5990 unique published articles initially identified, 20 full-text original studies met the inclusion criteria for the final review. The amount of abdominal adipose tissue was found to significantly affect enhancement, which suggests the possibility of reducing the CM dose to minimize adverse effects or toxicity. The injection rate of the CM, rather than the injection duration, was identified as the most critical factor, with important clinical implications. For scanners with slower acquisition speeds or longer scan durations, maintaining a fixed CM injection duration may optimize vascular phase acquisition. In contrast, faster scanners benefit from bolus tracking, which allows for improved differentiation between vascular phases. Additionally, administering a saline flush post-CM injection enhances arterial opacification while reducing the necessary CM dose. This systematic review highlights essential factors influencing contrast enhancement in angio-CT for dogs and provides a foundation for future research aimed at optimizing imaging protocols in veterinary medicine.